Proverbs and taboos as tools for women oppression among Yoruba of Southwest Nigeria (2020)
The relevance of women in every culture cannot be over-emphasized, this is because human society positioned them in an enviable place. They are described as home builders and house keepers. In any society, they wield enormous influence and, in some spheres, and cases, they have contributed strongly and positively to societal growth and transformation. However, as much as their influence is, many societies have consigned them to the background. Such societies have negative views and opinions about women through the use of proverbs and taboos that are largely inherent and culture based. Existing studies on women in Africa and Nigeria in particular have focused mainly on the contributions of women in every area of human endeavour with little attention paid to how proverbs and taboos that are satirical in nature have been used to reduce women to subordinate and second class citizens. Therefore, this study examined some selected proverbs and taboos among the Yoruba of Southwest, Nigeria and how they have negatively affected the rights of women and the way such rights can be enhanced in the Contemporary society. Recommendations were offered on how women can rise to the challenge of being relegated to the background so as to be able to contribute more meaningfully to the society without being culturally caged.